Cosmetic Product Packaging Return Program As A Strategy To Improve Gen-Z Consumers' Purchase Intention in Indonesia - Vivie Anggra Kusuma; Premananto, Gancar Candra (Dinasti Publisher, 2025)
This study aims to analyze the influence of packaging return programs using the Theory of Planned Behavior approach—comprising attitude, subjective norm, and perceived behavioral control—on Gen Z consumers’ purchase intention toward cosmetic products. A quantitative research design was employed, using an online questionnaire to collect data from 300 Gen Z respondents across various regions in Indonesia. All participants had experience purchasing cosmetic products and were aware of packaging return programs. The data were analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. This study evaluates the impact of a cosmetic packaging return program on Generation Z’s purchase intention in Indonesia, employing a Theory of Planned Behavior (TPB). Survey results from 300 respondents indicate that perceived behavioral control (PBC) is the strongest predictor of purchase intention (?=0.47), followed by subjective norms (?=0.45) and attitude (?=0.21) affects purchase intention for cosmetics with packaging return programs. The model’s strong explanatory power is confirmed by an R² value of 0.607 for purchase intention. These findings emphasize that marketing strategies for Indonesia’s cosmetic industry must align with sustainability issues by leveraging psychological and social approaches to foster responsible consumer behavior among Gen Z. The study provides practical implications for the industry to design eco-friendly initiatives that resonate with the values and lifestyles of younger generations.